Do returns to education matter to schooling participation? - Kingdon, G; Theopold, N (GPRG, 2006)
While it might be expected that demand for schooling will depend positively on the economic returns to education (ER) in the local labor market, in fact there is theoretical ambiguity about the sign of the schooling-ER relationship when households are liquidity-constrained. Whether the relationship is positive or negative depends on which effect dominates – the positive substitution effect of an increase in ER on years of education, or the negative income effect. For India, we find a positive relationship between the rate of return to education for adults in the local labor market and school attainment of girls and non-poor boys. The size of the effect of ER on years of education acquired is large for some groups. However, for poor boys the negative income effect dominates the positive substitution effect. Thus, while improved economic incentives for acquiring education have a positive impact on educational attainment of girls and non-poor boys, they worsen the educational attainment of poor boys. Policy implications are discussed.